2007
DOI: 10.1016/j.theriogenology.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a porcine circovirus type 2 infection on embryos during early pregnancy

Abstract: The aim of the present study was to assess the effects of porcine circovirus type 2 (PCV2) on porcine embryos and their receptor sows during the first 21 days of pregnancy. Hatched blastocysts exposed to 10 5.0 TCID 50 PCV2 per ml (strain 1121, fifth passage PK15) and negative control embryos were transferred to PCV2-immune receptor sows at the 7th day of the cycle. Two weeks after transfer (D21), the receptor sows were euthanized and embryos were recovered. They were assessed macroscopically for viability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 23 publications
1
33
1
1
Order By: Relevance
“…That this virus can be intermittently excreted by infected boars, semen may be an important means of transmission. The virus is also able to replicate in zona pellucida-free embryos, leading to embryonic death [23,24].…”
Section: Porcine Circovirus Type 2 (Pcv2)mentioning
confidence: 99%
“…That this virus can be intermittently excreted by infected boars, semen may be an important means of transmission. The virus is also able to replicate in zona pellucida-free embryos, leading to embryonic death [23,24].…”
Section: Porcine Circovirus Type 2 (Pcv2)mentioning
confidence: 99%
“…The virus is also able to replicate in the zona pellucida-free embryos, leading to embryonic death (Mateusen et al, 2004(Mateusen et al, , 2007. Delayed farrowing (>118 days of gestation) (LadekjaerMikkelsen et al, 2001) or pseudopregnancy (Josephson & Charbonneau, 2001) is less frequently observed with PCV2-associated reproductive failure.…”
Section: Porcine Circovirus Typementioning
confidence: 99%
“…In mature breeding animals, PCV2-associated reproductive failure can manifest as abortion, but it is more frequently associated with increased rates of mummified, macerated, stillborn and weak-born piglets (West et al ., 1999;O'Connor et al ., 2001). The experimental intrauterine infection with PCV2 resulted in virus replication in the fetuses (Sánchez et al ., 2001;Madson et al ., 2009a;Saha et al ., 2010), reproductive disease associated with fetal pathology (Johnson et al ., 2002) and early embryonic death during intrauterine PCV2 infection (Mateusen et al ., 2007). Other case reports of reproductive failure implicated PCV2 either as the sole agent or in conjunction with other reproductive disease agents (Brunborg et al ., 2007;Castro et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%